Pharmacokinetics of cefotiam administered intravenously and intramuscularly to healthy adults. - Brisson, A M (1984)
We studied the pharmacokinetics of cefotiam, a parenteral cephalosporin, at intravenous doses of 0.5, 1, and 2 g and intramuscular doses of 0.5 and 1 g in two groups of eight healthy adult volunteers. The concentrations of cefotiam in plasma were determined over a period of 5 or 6 h and in urine over 24 h, using high-pressure liquid chromatographic procedures. Plasma concentration-time data were fitted to a three-exponential equation for the intravenous administration, and after intramuscular administration, the data were analyzed by a two-compartment or a one-compartment open model. Over the above dosing range and routes of administration, cefotiam pharmacokinetics were essentially linear, with plasma clearances varying from 19.6 to 22.5 liters/h. No significant differences were observed with respect to the terminal half-life (1 h) and the area under the curve versus the dose. Intramuscularly injected cefotiam was 63 to 74% available. The fraction of dose excreted unchanged in urine (0.50 to 0.67) indicated a substantial nonrenal mechanism of elimination. The apparent volume of distribution (about 30 liters) was higher than those of other parenteral cephalosporins.